Pengaruh Model Pembelajaran Brain Based Learning Dipadukan dengan Mind Mapping terhadap Penguasaan Konsep Siswa - Mariyam Mariyam; Dede Nuraida (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Biology learning involves a process of thinking that is not separated from the human organs of the brain. One of the learning models that can maximize brain function is Brain Based Learning. Brain Based Learning is more optimal when combined with Mind Mapping in its stages. This study aims to examine whether or not there is a significant effect of Brain Based Learning model combined with Mind Mapping on mastery of students' concepts on plant tissue material in the XI – IPA SMAN 1 Tambakboyo academic year of 2017/2018. This study used quasy - posttest only desaign experiment, where there is one experiment class and one control class. In the experimental class was given treatment using Brain Based Learning learning model combined with Mind Mapping while control class only use conventional learning model. Score mastery of student concepts derived from the test of 15 multiple choice questions and 3 matter essay material plant tissue previously tested the validity and reliability. Student conception data was analyzed by one way Anova. The results showed that the experimental class had higher mean concept mastery than the control class. Thus, it can be concluded that the learning model of Brain Based Learning combined with Mind Mapping gives a positive impact on the mastery of students' concepts on plant tissue material in class XI – IPA SMAN 1 Tambakboyo. The results of this study provide recommendations for a more extensive review of the use of the BBL model combined with Mind Mapping for other materials in biology learning.